CLASSIFIED OBJECTIVES. - Littleton, A. C. (The Accounting Review, 1949)
The article presents comments of the author on an article by scholar Gordon W. Stead. The article by Stead is an interesting analysis of accounting ideology accompanied by a preliminary charting of idea interrelations. At the top of the chart stands integrity. It is the author's intention to show how the successive aspects of doctrine derive from this one fundamental concept, it being his view that this dependency is the direction of causation. It will be no detraction from his constructive contribution to the development of the concept of an integrated body of accounting thought to try here for a supplementary pattern one leaning toward a line of discussion he avoids when he chooses to show that rules of conduct derive from immutable principles. In this supplementary pattern it will be the view that principles may have been slowly distilled out of actions. This view would help to express the idea that accounting rules having first been fruits of tentative actions, grew in significance until they became guides to pre-determined actions. As these accounting actions grew increasingly diverse and complex, so did the attendant rules, customs, practices.